Influence of Structural State prior Quenching in Spring Steel - Kotous, Jakub; Salvetr, Pavel; Nacházelová, Daniela (Manufacturing Technology Journal, 2023)
Various structure states before quenching significantly influence final mechanical properties as well as the dispersion of chemical composition at the same steel grade. Therefore heat treatment with mechanical properties is specified in the technical delivery conditions. Even if the heat treatment is determined, different mechanical properties can be achieved. These differences are increasing in im-portance in high-strength applications like springs, cutting tools, safety, and load-bearing parts of automotive design et al. Because it has a direct impact on their lifetime. The structure consists of ferrite and cementite after spheroidization annealing prior quenching process. The cementite could be observed in various shapes, e.g. fine and large globular particles or the rest of the disintegrated lamellar shape. This article shows how these cementite morphologies affect the quenching behavior and final mechanical properties in high-strength spring steel 54SiCr6.
Keywords: Accelerated Spheroidization; ASR; Quenching; Spring steel; 54SiCr6